Eating disorders risk assessment in men who practice team sports - Baldó Vela, Daniel; Bonfanti, Noelia; Villarino Marín, Luis Antonio (Frontiers in Nutrition, 2022)
Introduction Eating disorders (EDs) are characterized by an overconcern about body weight and shape. Men who practice team sports have been systematically excluded from the high-risk eating disorders groups. This exclusion could be challenged based on misinformation about the prevalence of actual eating disorders within these athletes, with the previous evidence showing significant body image concerns among them and the under-diagnosis risk in populations of men. Objective To assess eating disorders risk in Spanish adult men who practice team sports. Methodology: An observational study was conducted with 276 athlete men aged between 18 and 55 years: 60.5% were team sports players and 39.5% were athletes of aesthetic, endurance, and weight-category sports. Data were collected via an online form including a general assessment sheet and four validated questionnaires: The Eating Habits Questionnaire for Athletes (CHAD), the Eating Attitudes Test (EAT-40), the Inventory of Eating Disorders (EDI-2), and the Body Shape Questionnaire (BSQ). Data analysis was conducted with the software IBM SPSS 28.0.0. Results About 20.36% of team sports players presented a clinical profile compatible with an ED diagnosis. There were no significant differences comparing EDs potential cases between team sports players and athletes playing sports categorized as high EDs risk. There were significant differences when analyzing the existence of EDs between the different groups of age, family pressure, and coach pressure. The U-value of the Mann–Whitney test presented significant differences when assessing the influence of BMI over the development of EDs. Conclusion Men who practice team sports may also be a high-risk group for the development of EDs. Being younger than 21 years, having a BMI larger than 25 kg/m2, and perceiving high-level pressure from the coach and/or family would be risk factors for EDs in men who practice team sports.